Marine genetic resources beyond national jurisdictions: Negotiatin options on intellectual property - Siva Thambisetty (South Centre, 2022)
Negotiations on marine biological diversity of areas beyond national jurisdiction (BBNJ) convene after a significant hiatus during which intellectual property monopolies have come under intense normative and pragmatic scrutiny. This paper historicises developments in legal arrangements over intellectual property and biodiversity to propose several negotiating options on the control, use and circulation of marine genetic resources of areas beyond national jurisdiction. The text-based options presented here operationalise an equitable approach taking into account the interests of low power groups, cross-cutting issues and the often ignored question of the ownership and use of marine genetic resources through intellectual property rights.
Keywords: 300